Factors Associated with Success in PARE Testing Among RCMP Officers - Seguin, Robert Andre (2015)
The purpose of this integrated article dissertation was to examine the predictive factors for success in the RCMP’s Physical Abilities Requirement Evaluation (PARE) in a retrospective observational study of 13, 709 unique records and a divisional subset of 620 for study two and three. Study one assessed the relative predictive power of the pursuit and body control times, while including covariates of height, weight, age. Significant (p< 0.05) and equally strong effects were for pursuit log odds (LO) of 2.95% CI [2.49, 3.11], and body control time LO of 2.80, 95% CI [2.51, 3.14] with a weak predictor , LO of 0.53, 95% CI [0.38, 0.72]. Not significant were height, weight, and sex with 99 % modeling accuracy. Study two compared sex and performance factors on six repeated PARE pursuit circuit laps for pacing for both divisional data (535 men, 85 women) and 61 age and BMI matched male/female pairs. Results divisional data: significant strong performance (pass/fail) effects F(1,616)=288.3, p< .00, partial η2 = .32 but weak sex (male/female) effects F(1,616) = 27.2, p =.03, partial η2= .01, interaction was significant, F(1,616)=50.7, p< .01, but weak, partial η2 = 0.014. Repeat laps were significant, F(3.7, 229)=195.1, p2=0.24; performance*laps interaction was significant F(3.7, 229)=4.5, p =.02, with weak effects, partial η2 = .007. Significant repeat lap contrasts were lap 1-2, strong effects and lap 2-3, lap 3-4, lap 4-5 weak effects, and not significant was lap 5-6. Results matched pairs data supported significant strong performance effects, F(1,118)=90.9, p2=.44 and weak sex effects, F(1,118)=13.5, p2=.10 not clinically significant. Significant repeat laps contrasts: laps 1-2, strong effect, lap 3-4 and lap 4-5, weak effect, lap 2-3 and lap 5-6 contrast was not significant. Men and women officers paced PARE repeat laps with slight ordinal interaction at lap three and six. The purpose of study three was to assess self-reported physical activity (PA) frequency and intensity as potential additional significant predictors of PARE success. PA frequency of 3.5 day/week, and intensity of 2.2 of 3.0, did not support additional predictors. There appears to be insufficient PA to affect a maximal test. Additional self-reported mode and dimensions of PA might increase PA predictability